Some Criminogenic Factors Affecting the Appearance of Corruption in Kosovo - Agnesa BEKA (Prizren Social Science Journal, 2020)
Corruption as a phenomenon, not only destroys the economic base of a country, but it violates the basis of its legal system, legislation, judiciary, public-private institutions, cultural and health institutions, social policies of society and others. In order to know and study the phenomenon of corruption, we must definitely stop at some criminogenic factors which have a significant impact on the appearance of the occurrence of corruption. Thus, corruption as a criminal occurrence is present throughout the history of the state and human society and as such has always been considered as an immoral and harmful social occurrence. Corruption is especially expressed in times of crisis of certain societies, but also along with the strengthening of the state, the development of business activities, the interference of the state in the economy and the bureaucratization of society it has found its housing of presence as a criminal occurrence. Today, the occurrence of corruption has become one of the obvious problems in most countries almost all over the globe. Factors that have influenced the appearance of this occurrence are numerous, such as: the transition of society, economic crises, unemployment, poverty, mass media, the war and the circumstances of the war, the unresolved housing problems, etc. For this, in recent times, corruption has been characterized as one of the most negative social occurrence. Cooperation between relevant state institutions and citizens for this type of criminal activity is extremely important for detecting corruption as a criminal offense.